Robotic-Assisted Nipple Sparing Mastectomy - Burns, Heather R.; McCarter, Jacob H.; King, Brody W.; Yu, Jessie Z.; Hwang, Rosa F. (Seminars in Plastic Surgery, 2023)
Minimally invasive approaches to breast surgery have evolved from endoscopic techniques to recent developments in robotic-assisted mastectomies. Initial studies on robotic-assisted nipple-sparing mastectomy (RNSM) have shown improved patient satisfaction and aesthetic outcomes with similar complication rates and oncological outcomes in selected patients. This chapter reviews techniques used and available data on complications and clinical outcomes for RNSM. Currently, RNSM is an investigational technique in the United States and should be performed in clinical trials with U.S. Food & Drug Administration approval to rigorously evaluate the safety and effectiveness of this approach.
Keywords: robotic-surgical platforms; nipple-sparing mastectomy; robotic surgery